Byron S. answered • 12/07/14

Tutor

5.0
(44)
Math and Science Tutor with an Engineering Background

Hi Brittany,

You've set up the problem correctly, so you probably made an arithmetic error or forgot to foil the square of the hypotenuse properly.

x

^{2}+ 92^{2}= (2x-23)^{2}x

^{2}+ 8464 = 4x^{2}- 92x + 5390 = 3x

^{2}- 92x - 7925The best way to solve this is probably the quadratic formula.

x = (92 ± √(92

^{2}-4*3*(-7925)) ) / 2*3x = (92 ± √(103564) ) / 6

x = (92 ± 321.81)/6

Subtracting will give a negative number, so we can ignore that

x = (92 + 321.81)/6

x = 413.81 / 6

x = 68.97 ft